2019
DOI: 10.1002/jcb.29059
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous interference of SP1 and HIF1α retarding the proliferation, migration, and invasion of human microvascular endothelial cells (HMEC‐1) under hypoxia

Abstract: Objective To investigate the regulation of special protein 1 (SP1) and hypoxia‐inducible factor‐1α (HIF1α) on human microvascular endothelial cells (HMEC‐1) under hypoxic conditions. Methods The expression of SP1 and HIF1α under normoxia and hypoxic conditions were assessed by Western blot. SP1 and HIF1α were knocked down by small interfering RNA (siRNA) under hypoxic conditions. The proliferation, migration, and invasion of HMEC‐1 were measured by cell counting kit 8, 5‐ethynyl‐2′‐deoxyuridine and Transwell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…If the retinal blood vessels in Phase I formed normally, the malignant proliferation of blood vessels caused by peripheral retinal ischemia in phase II can be avoided [3], thus ROP children could obtain better visual function. Studies have shown that human retinal angiogenesis is related to the proliferation, migration and angiogenesis of microvascular endothelial cells [2,22], the HMEC-1 is a recognized model of vascular endothelial cells [11,23]. Therefore, we established a model of HMEC-1 induced by 40% hyperoxia in vitro to simulate the relatively hyperoxia environment of phase I ROP, and found that the biological behaviors of HMEC-1 such as cell proliferation, migration and angiogenesis were inhibited in 40% hyperoxia environment.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…If the retinal blood vessels in Phase I formed normally, the malignant proliferation of blood vessels caused by peripheral retinal ischemia in phase II can be avoided [3], thus ROP children could obtain better visual function. Studies have shown that human retinal angiogenesis is related to the proliferation, migration and angiogenesis of microvascular endothelial cells [2,22], the HMEC-1 is a recognized model of vascular endothelial cells [11,23]. Therefore, we established a model of HMEC-1 induced by 40% hyperoxia in vitro to simulate the relatively hyperoxia environment of phase I ROP, and found that the biological behaviors of HMEC-1 such as cell proliferation, migration and angiogenesis were inhibited in 40% hyperoxia environment.…”
Section: Discussionmentioning
confidence: 98%
“…HMEC-1 were purchased from American Type Culture Collection (ATCC, Rockefeller of Maryland, the certi cate and STR test result are supplemented in additional le 1,2). According to the previous experimental practice of our research group [11]. The cell culture medium was prepared in MCDB131 medium containing 10% fetal bovine serum (FBS, Gibco, USA), 1% antibiotics (including streptomycin 0.1mg/mL, and penicillin 100U/mL, Gibco), 2mM glutamine(25030, Gibco) and 1μg/ml hydrocortisone (M3451, Abmole, USA) [12].…”
Section: Hmec-1 Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…HMEC-1 cells were purchased from American Type Culture Collection (ATCC, Rockefeller of Maryland), and the certificate and STR test results are supplemented in Additional files 1 and 2. According to the previous protocol established by our research group [11], cells were cultured in MCDB131 medium containing 10% foetal bovine serum (FBS, Gibco, USA), 1% antibiotics (including streptomycin 0.1 mg/mL and penicillin 100 U/mL, Gibco), 2 mM glutamine (25,030, Gibco) and 1 μg/mL hydrocortisone (M3451, Abmole, USA) [12]. A working solution of 10 mM haem (51,280, Sigma, USA) was prepared in 20 mM NaOH (diluted in PBS) [9].…”
Section: Hmec-1 Cell Culturementioning
confidence: 99%
“…HMEC-1 cells were seeded in Millicell plates (1.5 × 10 4 / well, 200 μL) for 12 h and then cultured under normoxic conditions until the cells adhered to the well bottoms as previously described [11]. The cells were then subjected to the indicated treatments (0 μM haem, 20 μM haem or vehicle) and cultured under normoxic or hyperoxic conditions for 48 h (the medium was changed every 24 h).…”
Section: Immunofluorescence (If) Assaymentioning
confidence: 99%